Estimation of vehicular emissions and fuel consumption on road links using HDM-IV in Ghana - A case study on the George Walker Bush Motorway (14.1km) Accra - Bonsu, Ernest Osei (2017)
A thesis submitted to the Department of Civil Engineering, College of Engineering in partial fulfillment of the requirements for the degree of Master of Science Road and Transportation Engineering.